Substitution in the Labor Force - الفيتوري, د.عطيه المهدي (Dirasat in Economics and Business, 1982)
The aim of this paper is to focus the attention on the problem of manpower shortage in the Libyan economy, and to suggest some ways of solving or at least minimizing this problem. The paper showed the increasing shortage of manpower over the years, because the demand for labor is increasing by higher rates than the supply of Libyan manpower. The structure of supply of manpower in Libya during the year 1980 showed that the problem is very acute, especially in the skilled labor force; for example, the Libyan manpower in the engineers category form less than 14% of the total engineers working in Libya, the percentage of the Libyan medical doctors is even less and it is less than 9% of the total medical doctors working in the country. This situation affects the economy in several ways, and therefore, the paper suggests that the substitution of Libyans for foreigners will help the economy in several ways: 1. It minimizes the cost of production of goods and services. 2. It increases the efficiency of the labor factor. 3 It facilitates undertaking any activity and communications. 4. It relieves the balance of payments from the increasing transfers out of the country by the foreign Labor force. 5. It minimizes the social and political problems arising from the presence of the increasing number of the foreign labor. 6. It relieves the public budget from the increasing expenditures. The paper suggests four methods to undertake this substitution: 1. Training and Education. 2. Reallocation of the Libyan manpower. 3. Applying production functions that favour the capital-intensive techniques. 4. The increase of women participation in the labor force.